Poetry criticism : excerpts from criticism of the works of the most significant and widely studied poets of world literature / Volume 74 - 4 0 16; Lee, Michelle; 5 (Detroit : Thomson/Gale, 2007)
Contains alphabetically arranged articles that provide critical excerpts and biographical information on four of the world's most frequently discussed and studied poets, including Lewis Carroll, Martin Espada, Bob Kaufman, and W.D. Snodgrass; and features includes cumulative author, nationality, and title indexes.
Includes bibliographical references and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Poetry;Poetry;Poets;Poetry;Poetry;Poets -- Bio-bibliography.;Biography.;Bio-bibliography.;Biography.; 20; 2